Getting a balance in the life satisfaction determinants of full-time and part-time European workers - Henriques, C.O.; Marcenaro-Gutierrez, O.D.; Lopez-Agudo, Luis Alejandro (Economic analysis and policy, 2020)
This paper explores the trade-offs between four different aspects of European workers’ life satisfaction (satisfaction with education, the present work, family life and social life), to reach balanced optimal levels across these features. This analysis was performed separately for different profiles of workers, i.e. full-time and part-time workers in 34 different European countries, differentiated by gender. The methodology employed for this purpose couples econometric and multiobjective interval programming approaches, enabling to assess the compromises of specific aspects of workers’ personal and working conditions. Our findings indicate that current full-time working environments do not enable to foster higher levels of workers’ life satisfaction with more than one child. Moreover, full-time (unlike part-time) working activities allow reaching worse levels across all measures of life satisfaction under analysis in a best-case scenario. This outcome suggests a change of paradigm where workers are keen on sacrificing other aspects of life satisfaction (namely their earnings and benefits) if this means having a better compromise of their personal and working lives. It is clear that promoting one-sided policies that only account for workers’ satisfaction with their jobs and careers, without explicitly encompassing family values, affects fertility rates and population ageing, raising awareness of the importance of family work in policy-making.